SISTEM INFORMASI PELAYANAN ADMINISTRASI KELURAHAN BERBASIS WEB DENGAN FASILITAS E-COMPLAINT MENGGUNAKAN TELEGRAM BOT - Panca Rahardiyanto; Zuhri Prihandono (STMIK YADIKA BANGIL, 2021)
Abstract : public service is the provision of services carried out by the government as the realization of state administration to meet the need of the community accordance with applicable regulatons / laws. Pogar village’s one of the government agencies located in Bangil district, Pasuruan regency. The method used in this research is rapid application development. Collecting data through interviews with officers from the Pogar village office, observing daily services to the community at the Pogar village office. With this system,it is hoped that it will facilitate the public in requesting services and reporting through the telegram application and making it easier for officers to administer documents at the village office. Keywords : Information Systems, Public Services, Telegram Bot, RAD (Rapid Application Development)